TRAGEDI 1965 SEBAGAI LANDASAN FABULA DAN SYUZHET DALAM CERPEN “SURAT NURLAN DAULAY KEPADA JUNJUNGAN JIWANYA” KARYA MARTIN ALEIDA: KAJIAN FORMALISME RUSIA - Penggalih, Aura Zahradiva (Metahumaniora, 2026)
Although literary works are seen as fictional products, discourses about the reality of life are not completely absent. Armed with the creativity of language, writers often use historical facts as the basis of storytelling in their works, which are then referred to as fabula. Martin Aleida in his short story entitled "Surat Nurlan Daulay Kepada Junjungan Jiwanya" also uses historical facts as the basis for fabula in storytelling.Through a qualitative method with a close reading technique and note-taking approached combining with a Russian formalism study, this study aims to reveal historical facts of the 1965 Tragedy used by Martin Aleida in the short story of "Surat Nurlan Daulay Kepada Junjungan Jiwanya". The results of the study indicate that there are five historical facts related to the 1965 Tragedy trilogy according to Adam (2004) in the short story, including the Gerakan 30 September, the suppression of the PKI, Gerwani's black propaganda and violence against female political prisoners, Operasi Kalong, and the exile of political prisoners during the New Order on Buru Island. These five historical facts are defamiliarized and then processed into syuzhet in the narrative elements of the story.